(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article describes the role of active investment in the dynamics of social welfare. Studies have been carried out to enhance local and foreign investment in Uzbekistan and relevant recommendations have been given. Conclusions are drawn about the impact of investments on social welfare.